Eldecalcitol prevents endothelial dysfunction in postmenopausal osteoporosis model rats. Issue 2 (4th November 2015) - Serizawa, Kenichi; Yogo, Kenji; Tashiro, Yoshihito; Takeda, Satoshi; Kawasaki, Ryohei; Aizawa, Ken; Endo, Koichi
Abstract : Postmenopausal women have high incidence of cardiovascular events as estrogen deficiency can cause endothelial dysfunction. Vitamin D is reported to be beneficial on endothelial function, but it remains controversial whether vitamin D is effective for endothelial dysfunction under the treatment for osteoporosis in postmenopausal women. The aim of this study was to evaluate the endothelial protective effect of eldecalcitol (ELD) in ovariectomized (OVX) rats. ELD (20 ng/kg) was orally administrated five times a week for 4 weeks from 1 day after surgery. After that, flow-mediated dilation (FMD) as an indicator of endothelial function was measured by high-resolution ultrasound in the femoral artery of living rats. ELD ameliorated the reduction of FMD in OVX rats. ELD inhibited the increase in NOX4, nitrotyrosine, and p65 and the decrease in dimer/monomer ratio of nitric oxide synthase in OVX rat femoral arteries. ELD also prevented the decrease in peroxisome proliferator-activated receptor gamma (PPARγ) in femoral arteries and cultured endothelial cells. Although PPARγ is known to inhibit osteoblastogenesis, ELD understandably increased bone mineral density of OVX rats without increase in PPARγ in bone marrow. These results suggest that ELD prevented the deterioration of endothelial function under condition of preventing bone loss in OVX rats. This endothelial protective effect of ELD might be exerted through improvement of endothelial nitric oxide synthase uncoupling, which is mediated by an antioxidative effect through normalization of vascular PPARγ/NF-κB signaling.